On dissociative amnesia - T. N. Maksimova; S. V. Prokhorova; V. A. Demidova (Неврология, нейропсихиатрия, психосоматика, 2018)
The paper describes a clinical case of dissociative amnesia in a 22-year-old patient. A marked hysterical radical was observed in premorbid. As a result of the psychotraumatic situation, the patient twice lost memories of the events of his life, could not remember his name, place of residence. At the same time, his ability to memorize new information, training knowledge, and some dance skills were preserved. Instrumental examinations detected no organic pathology. Memory in both cases was fully restored within a few months. Patients with similar symptoms were increasingly encountered in psychiatric practice. At the same time, there are different viewpoints on the occurrence of such symptoms. It is obvious that the problem of dissociative amnesia is relevant and requires further investigation.